Variabilidade espacial de atributos físicos em um Latossolo Vermelho distrófico sob semeadura direta em Selvíria (MS) - Souza, Z. M.; Silva, M. L. S.; Guimarães, G. L.; Campos, D. T. S.; Carvalho, M. P.; Pereira, G. T. (Sociedade Brasileira de Ciência do Solo, 2001)
In a natural landscape, the soils present a wide variation on morphological, physical, chemical and mineralogical properties due to several soil formation factors. In a cultivated landscape others sources of variation may be present, such as anthropogenical processes. The knowledgement of these variations is important to soil survey, development of sampling designs and soil management practices. This work aimed to study the spatial variability of some physicals attributes of a Dystrophic Red Latosol cropped in no tillage system. It was conducted in August and September, 1999 at the Experimental Station of UNESP - Ilha Solteira campus, located in Selvíria (MS). Soil sampling was accomplished according to an appropriate geostatistical analysis design defined as a grid with 150 m length in South direction and 30 m width in North direction. There were 103 points equaly spaced, 10 m apart from each other, and 39 points equaly spaced, 1 m apart from each other, randomly distributed in the grid. From each point defined according to the grid it was taken one sample at the 0,00-0,05 m and one at the 0,15-0,20 m depths. The results were firstly evaluated by exploratory statistics analysis calculating average, frequency distribution, variance, coefficient of variation, and coefficients of kurtosis and skewed. Subsequently, the spatial dependence was verified through semivariogram. The microporosity, total porosity and bulk density attributes followed normal distribution, while the macroporosity and penetration resistance followed the lognormal distribution. Soil moisture presented distribution closer to the lognormal. The largest variation coefficient was verified for macroporosity and penetration resistance. The other evaluations presented variation coefficient below 10%. It was observed moderate spatial dependence for every attribute studied. The spatial dependence reachness varied from 8,36 m (soil moisture) to 58,80 m (penetration resistance).

Em uma paisagem natural, os solos apresentam ampla variação de propriedades morfológicas, físicas, químicas e mineralógicas, resultante da superposição dos diversos fatores de formação envolvidos. No caso de uma paisagem cultivada, existem outras fontes de heterogeneidade no solo devidas ao manejo exercido pelo homem. O conhecimento dessa variação é importante para o levantamento e classificação dos solos, desenvolvimento de esquemas de amostragem e definições de práticas de manejos. O presente trabalho foi realizado em agosto e setembro de 1999, na Fazenda Experimental de Ensino e Pesquisa da Faculdade de Engenharia de Ilha Solteira/UNESP, localizada em Selvíria (MS), com o objetivo de estudar a variabilidade espacial de alguns atributos físicos de um Latossolo Vermelho distrófico, cultivado no sistema de semeadura direta. A amostragem do solo foi realizada de acordo com um desenho apropriado para a análise geoestatística na forma de uma malha em uma área de 150 m de comprimento, na direção sul, e 30 m de largura, na direção norte, totalizando 103 pontos eqüidistantes de 10 em 10 m e 39 pontos eqüidistantes de 1 m distribuídos aleatoriamente pela malha. De cada ponto definido pela malha, retiraram-se amostras nas profundidades de 0,00-0,05 m e 0,15-0,20 m. Os dados foram avaliados primeiramente por uma análise estatística exploratória, calculando-se a média, distribuição de freqüência, variância, coeficiente de variação, coeficiente de assimetria e coeficiente de curtose. Posteriormente, a dependência espacial foi verificada por meio de semivariogramas. Os atributos microporosidade, porosidade total e densidade do solo seguiram a distribuição normal, enquanto a macroporosidade e a resistência à penetração seguiram a distribuição lognormal. A umidade do solo apresentou uma distribuição mais próxima da lognormal. Os maiores coeficientes de variação foram observados para a macroporosidade e resistência à penetração, tendo as demais variáveis apresentado coeficiente de variação abaixo de 10%. Foi observada uma dependência espacial moderada para todas as variáveis estudadas. O alcance da dependência espacial variou de 8,36 m (umidade do solo) a 58,80 m (resistência à penetração).
Spatial variability of physics attributes on a distrophic Red Latosol under no tillage system in Selvíria (MS)
Keywords: frequency distribution; variation coefficient; geostatistic; semivariogram; spatial dependence; distribuição de freqüência; coeficiente de variação; geoestatística; semivariograma; dependência espacial